PERANCANGAN LAYANAN SYSTEM INFORMASI DALAM PROGRAM BIMBINGAN DAN KONSELING BERBASIS DESKTOP TINGKAT SMK - Nurbaeti Nurbaeti; Herdi Herdi (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2021)
Counseling guidance is really needed in a school that can include data on student biodata information but it involves all important aspects such as grades, discipline, attendance, extracurricular activities, and so forth. Data management in counseling guidance is still manual, so it requires more time and more complicated processes. The use of computer application programs in managing student data can also improve school images. The use of computer application programs makes it easy for teachers to manage student data, especially in the management of counseling guidance. The Counseling Guidance Information System is intended to facilitate the Counseling Guidance teacher in registering students who have consulted. The stored data is expected to be utilized by the school in making conclusions and decisions regarding the problems and developments of students in the future. Regarding student privacy, there is a security system where not all teachers can have access to the system. The basic concept of information service systems (Hutahean, 2014) is a collection consisting of several components which are often referred to as building blocks, namely: a) input blocks, b) output blocks, c) technology blocks, d) model blocks, e ) database blocks, f) control blocks.